Synergistically enhanced charge separation in BiFeO3/Sn:TiO2 nanorod photoanode via bulk and surface dual modifications - Huang, Jing (2021)
Charge separation is regarded as a vital factor determining the photoelectrochemical (PEC) performance of TiO2 photoanode. Herein, for the first time, the synergistic effect between Sn doping and ferroelectric BiFeO3 (BFO) coating in BFO/Sn:TiO2 composite photoanode for enhanced PEC performance is reported. The Sn doping leads to enhanced charge carrier density due to efficient charge separation. After the deposition of ferroelectric BFO thin film, the charge-separation efficiency (ηsep) is further enhanced because of spontaneous polarization of the BFO layer. More importantly, the PEC performance could be further improved by positive polarization of the BFO/Sn:TiO2 composite photoanode, achieving remarkable photocurrent density (Jph) of 1.76 mA cm−2 at 1.23 V vs. reversible hydrogen electrode and high stability. This work indicates that the dual modification (i.e. Sn doping in bulk and ferroelectric BFO thin film deposition on the surface) holds a great promise in improving the PEC performance of photoanodes by promoting charge separation, which can be extended to other common photoanode materials, such as Fe2O3 and BiVO4.